Nano-structured metal-semiconductor-metal photo-detectors for enhanced light absorption - Das, Narottam; Masouleh, F.; Mashayekhi, H. (The 5th International Conference on Computers and Devices for Communications 2012 (CODEC2012), 2012)
Nano-structured metal-semiconductor-metal photodetectors (MSM-PDs) are enable to assist in future high-speed communication devices achieving high responsivity-bandwidth characteristics. Finite difference time-domain (FDTD) method is used to calculate the light absorption enhancement of nano-grating assisted MSM-PDs near the design wavelength by varying detector's geometrical parameters in comparison with a conventional device. The substrate containing apertures and the nano-gratings are optimized in thickness to trigger extraordinary optical transmission. Besides, it demonstrates how the coupling condition satisfies the oscillating charge densities evolution to the surface plasmon polaritons under illumination of polarized light. The simulation results confirm that the light absorption enhancement of nano-grating assisted MSM-PDs is ~13.5-times better than the conventional MSM-PDs.